Performa dan Profil Kuning Telur Itik yang Diberi Pakan dengan Suplemen Tepung Bawang Putih dan Limbah Udang - Asep Sudarman; Denbeti Noviani; Rita Mutia (Jurnal Ilmu Pertanian Indonesia, 2018)
This study aimed to investigate the effect of adding garlic and shrimp waste in the ration on the duck performance and lipid profile of yolk. The animals used were 36 ducklings of 19-week old that were randomly placed in 12 battery cages. The experimental design used in this study was a completely randomized design with four treatments and three replicates. The treatments were R0 (control) = Commercial ration, R1 = Commercial ration + 2% garlic, R2 = Commercial ration + 2% shrimp waste, and R3 = K + 1% garlic + 1% shrimp waste. The results showed that the addition of garlic or shrimp waste resulted in a higher egg production (P<0.05) than that of control group, but the combination of garlic and shrimp waste had no significant effect on egg productuon. The addition of garlic, shrimp waste, or a combination of garlic and shrimp waste increased yolk color score significantly (P<0.05). Giving garlic or shrimp waste, and combination of garlic and shrimp waste significantly (P<0.05) lowered the cholesterol content of the eggs compared to controls. The addition of shrimp waste increased the unsaturated fatty acids content of duck eggs, and at the same time increased saturated fatty acid content.